Hubungan Komitmen Manajer Proyek Terhadap Keberhasilan Proyek Konstruksi Gedung di Wilayah Perkotaan Sarbagita - Ayu Mirayani Pradnyadari Ni Luh Made (Jurnal Ilmiah Telsinas, 2021)
Project manager is leader of project organization who take responsibility for whole projects in purpose to get it wrapped succesfully. Commitment is an important thing for a project manager. A project manager who isn't committed might impact into the failure of a project, as well as inflated costs, late project completion and unmet quality. This studi aimed to analyze the relationship between project manager commitment to the success of building construction projects. This research was conducted on a building construction project in the Sarbagita Urban area (Denpasar City, Badung Regency, Gianyar Regency, and Tabanan Regency). Collecting data through a survey using a questionnaire. Respondents selected based on the purposive sampling method, includes the criteria of people who have been / are handling the implementation of building construction projects, have at least three years of experience, have the position of project manager, Site Manager, Operational Manager, which includes 60 respondents. Data processing using Partial Least Squares analysis with SmartPLS 3.0 software. The results of the analysis show that the Project Manager's Commitment has a positive and significant effect on the success of building construction projects. The most dominant commitment variable was a career commitment of 0.241, followed by a normative commitment of 0.237, a continuance commitment of 0.228, and an affective commitment of 0.217